Warming promoted CH4 absorption compared with precipitation addition in typical steppe in Inner Mongolia - Chen, Xuemeng; Wan, Zhiqiang; Gu, Rui; Ganjurjav, Hasbagan; Hu, Guozheng; Gao, Qingzhu; Chun, Xi; Zhou, Haijun; Hai, Chunxing (Frontiers in Ecology and Evolution, 2023)
Introduction: Climate change, characterized by rising temperatures and changing precipitation patterns, has emerged as a significant global concern. Particularly, the warming potential of CH4 is 28 times greater than that of CO2, leading to an increased focus on its impact. Among various ecosystems, grasslands exhibit a high vulnerability to climate change. Grassland in Inner Mongolia is an important component of the typical grassland in Eurasian, and there was evidence that warmer and more precipitation in this area in future. Methods: In this study, we utilized an open-top chamber (OTC) to conduct warming and precipitation experiments on a representative steppe located in Inner Mongolia in 2011. From 2017 to 2019, we monitored various factors, including soil temperature, moisture, CH4 flux, community characteristics, soil carbon nitrogen content. Subsequently, we analysed the response of CH4 flux and its influencing factors to warming and precipitation in this typical steppe. Results: The soil in the typical steppe acted as a CH4 sink. In 2018, CH4 flux during the growing season and t during the non-growing season were -59.31 and -21.21 under C, -56.55 and -31.17 under T, -41.34 and -24.93 under P, -50.09 and -26.51 ug C·m-2·h-1 under TP respectively. Warming stimulated absorption of CH4 during the non-growing season (25.8%), while the addition of precipitation hindered CH4 absorption during the growing season (76.37%). Warming and precipitation addition decreased the percentage of CH4 absorbed in growing season and increased that in non-growing season which account 67.66% and 32.34% under C, 59.81% and 40.19% under T, 62.71% and 37.29% under P, 62.03% and 37.97% under TP respectively. Soil temperature exhibited a positive correlation with CH4 flux (P<0.001), while the dominance of Leymus chinensis (IV-L.c.) exhibited a negative correlation with CH4 flux (P<0.01). Moreover, NH4+-N displayed a positive correlation with CH4 flux (P<0.05). Conclusion: The findings suggest that CH4 absorption in a typical steppe may increase in a warmer future, and warming is conducive to the absorption of CH4 in the non-growing season. Not only abiotic factors had an impact on CH4 absorption, but also changes in community composition. Consequently, further exploration of the underlying mechanisms is warranted.